Kurdish High School Students' Perceptions on Integrating AI to Mitigate Anxiety and Cultivate Motivation - Shvan Samad Youns; Parween Shawkat Kawther (Zanco Journal of Human Sciences, 2026)
Artificial intelligence tools are adaptive technological systems that personalize learning experiences through intelligent feedback mechanisms. Despite growing availability, AI tools are rarely used in EFL classrooms across the Kurdistan Region, where educators continue relying on traditional instruction methods. This approach limits student engagement and creates learning barriers, particularly for students struggling with elevated anxiety levels. This descriptive study examines the impact of AI tools on motivation and the reduction of learning anxiety among Kurdish high school students. The research employed a quantitative approach using a five-point Likert scale questionnaire distributed to 301 students from grades 10-11 across six English systematic schools during the 2024-2025 academic year. This study measured student perceptions of AI's impact rather than experimentally verified outcomes. Reliability testing confirmed a Cronbach's alpha of 0.865, with data analysis conducted using SPSS (Version 27). Findings show that AI tools substantially boost student motivation, as 74.1% agreed that AI makes English learning more enjoyable compared to traditional methods. Adaptive feedback, interactivity, and self-paced practice were features students reported as improving engagement. Some students had challenges with technical issues; however, many of them felt far more secure by rehearsing tough concepts privately. Furthermore, AI tools fostered psychologically safe learning environments that reduced both academic and social anxieties. Nevertheless, some students reported that unfamiliarity with AI technology initially heightened stress levels, suggesting that gradual implementation with proper support is essential. The research emphasizes the importance of careful AI integration and thoughtful instructional design. Properly implemented AI tools can effectively bridge traditional anxiety-inducing teaching methods with supportive, student-centered learning environments.